A marcação de relações textuais em textos de gêneros do domínio jornalístico: uma abordagem modular - Rejane Julia Duarte (2008)
This research aims at main goal analyzing how the markingprocess of textual relations work in texts pertaining to two particularorders in journalism domain. Coming from the hypothesis that textsfrom different orders tend to present differences when it comes to themarking process cited above, we investigate the related organizationform of two texts, taking as reference the theoretical-methodologicalmodel known as Modular Analysis Model. Duo to the corpus selectedfor this research, news and articles of opinion published in four printednewspapers and from my interest, which is centered on the descriptionand explanation of the different textual relations on the speechcomposition, I also try later to approach the hierarchical dimension,which provides the hierarchical structures of all possible texts, and therelated organization, concerning the determination of textual relationsand the role of connectors on the marking process and also on theestablishment of these relations, as a route of analysis.